2012
DOI: 10.1136/jnnp-2012-303258
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of age with the ischaemic penumbra, leptomeningeal collateral circulation and haemodynamic variables in acute stroke: a pilot study

Abstract: These findings, described for the first time in a clinical cohort using whole brain CT perfusion and concomitant vascular imaging, suggest that age has a differential effect on acute tissue compartments in the wake of a preserved collateral vascular response and haemodynamic parameters. In agreement with the preclinical literature, the results point to a distinct tissue response to acute ischaemia in the ageing brain and merit validation studies in larger cohorts, particularly in relation to clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…The discrepancies may be due to the difference in animal strains, animal sexes, or ischemic models used in the studies. Several clinical studies 7, 26 demonstrated age negatively correlated with the size of either the ischemic lesion or the penumbral area in stroke patients, which is consistent with the results from our studies. Despite discrepancies in histological outcomes, there is agreement in most preclinical and clinical studies that functional (behavioral) stroke outcomes are worse in aged cohorts 2, 6, 22, 27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The discrepancies may be due to the difference in animal strains, animal sexes, or ischemic models used in the studies. Several clinical studies 7, 26 demonstrated age negatively correlated with the size of either the ischemic lesion or the penumbral area in stroke patients, which is consistent with the results from our studies. Despite discrepancies in histological outcomes, there is agreement in most preclinical and clinical studies that functional (behavioral) stroke outcomes are worse in aged cohorts 2, 6, 22, 27 .…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that aged male mice have smaller infarct volumes but worse functional recovery when compared with young mice 46 , which is consistent with clinical data 7 . However, the underlying mechanism for this discrepancy in histological and functional outcome is unclear.…”
Section: Introductionsupporting
confidence: 90%
“…Therefore, impairments in function are likely regardless of cortical health, diminishing the likelihood of strong volume-function correlations with regards to cortical and total volumes acutely [28]. This is particularly true with regards to the aged rodent model utilized herein as cortical volumes are typically larger in this model due to reduce collateralization with age and therefore, increased tissue susceptibility to ischemia [29]. There is less discrepancy in collateral flow with regards to the striatum between young and aged rodents, resulting in more uniformity when considering striatal infarct volumes.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples of attempts to examine the factors that predict independent survival5 or recovery of language function in those with aphasia,6 as well as outcomes in a number of stroke subtypes or treatment scenarios. There are studies examining the effect of important variables such as age,7 cognitive impairment4 and infection8 on outcomes. These attempts to predict outcomes based on key variables are important for patients, carers and clinicians in defining appropriate care but also for stratification of patients in treatment studies.…”
mentioning
confidence: 99%